MICROWAVE DRYING OF ALOE VERA (ALOE BARBADENSIS MILLER): MATHEMATICAL MODELING, KINETICS AND MASS TRANSFER ASPECTS - Srinivasan, G.; Baskar, R. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Aloe vera has extensive application in food and pharmaceutical industry in fact contains 97 percent of water. Itâ€™s perishable in nature and poor shelf life makes it essential to study the drying characteristics of aloe vera. The objective of this present study is to investigate the effect of different microwave (MW) respective power levels (180 , 360 ,540 , 720 and 900 Watts ) regarding theÂ moisture ratio (MR), drying rate (DR), effective moisture diffusivity (EMD), specific energy consumption (SEC) and drying efficiency (DE) of aloe vera. The drying process took 70 - 26 .5 minutes for attainment of equilibrium moisture content. A mathematical model done by Midilli et al.Â is considered to be the best and most suitable for a drying conditions among the various thin layer models. The effective moisture diffusivity value at 180 Watts (W) of MW power was found as 4.5 Ã— 10-8 m2/sec. while it was raised to 9.45 x10-7 m2/sec at 900 W in this study. Lowest energy consumption 1.4 MJ/Kg water and maximum drying efficiency occurred at higher microwave power level 900 Watts due to less drying duration (time).